Pengaruh Harga, Kualitas Pelayanan Dan Kualitas Produk Terhadap Kepuasan Pelanggan Pada PT. Literasi Nusantara Abadi Grup - Waras Widodo Saputro; Muhammad Mansur; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstrack The purpose of this study was to determine and analyze the effect of price, service quality and product quality on customer satisfaction. Primary data collection using questionnaires and secondary data collection using a survey of consumers who visit PT. Abadi Literacy Group recorded 71 consumers as a population. using purposive sampling technique with criteria.The results in this study indicate that there is a partial effect of price on customer satisfaction, service quality partially affects customer satisfaction, product quality partially affects customer satisfaction Keywords: Price, Service Quality, Product Quality and Customer Satisfaction